Chapter 4 The Administration of Bicameral Parliaments - Christiansen, Thomas; GRIGLIO, Elena; Lupo, Nicola (Taylor & Francis, 2023)
Parliaments are complex and pluralistic organizations. They are called upon to represent political and territorial diversities and to cover at least potentially any subject matter. In the case of bicameral parliaments, the level of complexity is at least doubled, as the internal structure is duplicated in two parallel Houses: these may either be of similar or of dissimilar composition, they usually hold diﬀerent functions and act independently from one other. This chapter aims to provide a comparative analysis of the various solutions that parliaments have arrived at in addressing this universal challenge. It presents an overview of the three main formats resulting from the comparative analysis of bicameral parliamentary administrations. The chapter analyses the features of each of these formats, examining the motivations behind choices in favour of a more divided or a more integrated administrative arrangement in bicameral parliaments.